Molecular Response of the Brain to Cross-Generational Warming in a Coral Reef Fish - Bernal, Moisés A.; Schmidt, Elliott; Donelson, Jennifer M.; Munday, Philip L.; Ravasi, Timothy (Frontiers in Marine Science, 2022)
Ocean warming is a threat to marine biodiversity, as it can push marine species beyond their physiological limits. Detrimental effects can occur when marine poikilotherms are exposed to conditions beyond their thermal optima. However, acclamatory mechanisms, such as plasticity, may enable compensation of detrimental effects if warming is experienced during development or across generations. Studies evaluating the molecular responses of fishes to warming have mostly focused on liver, muscle and gonads, and little is known about the effects on other vital organs, including the brain. This study evaluated the transcriptional program of the brain in the coral reef fish Acanthochromis polyacanthus, exposed to two different warming scenarios: +1.5°C and +3.0°C, across successive generations. Fish were exposed to these conditions in both developmental (F1 and F2) and transgenerational settings (F2 only), as well as a treatment with step-wise warming between generations. The largest differences in gene expression were between individuals of the first and second generation, a pattern that was corroborated by pairwise comparisons between Control F1 and Control F2 (7,500 DEGs) fish. This large difference could be associated with parental effects, as parents of the F1 generation were collected from the wild, whereas parents of the F2 generation were reared in captivity. A general response to warming was observed at both temperatures and in developmental and transgenerational treatments included protein folding, oxygen transport (i.e. myoglobin), apoptosis and cell death, modification of cellular structure, mitochondrial activity, immunity and changes in circadian regulation. Treatments at the highest temperature showed a reduction in synaptic activity and neurotransmission, which matches previous behavioral observations in coral reef fishes. The Transgenerational +3.0°C treatment showed significant activation of the gene pls3, which is known for the development of neuro-muscular junctions under heat-stress. F2 samples exposed to step-wise warming showed an intermediate response, with few differentially expressed genes compared to developmental and transgenerational groups (except for Transgenerational +1.5°C). In combination with previous studies on liver gene expression, this study indicates that warming produces a molecular signature of stress response in A. polyacanthus that is influenced both by the intensity of warming as well as the duration of exposure.